Sick Note A History of the British Welfare State - Millward, Gareth (Oxford University Press, 2022)
Sick Note is a history of how the British state asked, 'who is really sick?' Tracing medical certification for absence from work from 1948 to 2010, it shows that doctors, employers, employees, politicians, media commentators, and citizens each concerned themselves with measuring sickness. At various times, each understood that a signed note from a doctor was not enough to 'prove' whether someone was 'really' sick. Yet, with no better alternative on offer, the sick note survived in practice and in the popular imagination-just like the welfare state itself. Sick Note reveals the interplay between medical, employment, and social security policy. The physical note became an integral part of working and living in Britain, while the term 'sick note' was often deployed rhetorically as a mocking nickname or symbol of Britain's economic and political troubles. Using government policy documents, popular media, internet archives, and contemporary research, this book covers the evolution of medical certification and the welfare state since the Second World War, demonstrating how sickness and disability policies responded to demographic and economic changes-though not always satisfactorily for administrators or claimants. Moreover, despite the creation of 'the fit note' in 2010, the idea of 'the sick note' has remained. With the specific challenges posed by the global pandemic in the early 2020s, Sick Note shows how the question of 'who is really sick?' has never been straightforward and will continue to perplex the British state.